Effects of Sintering Temperatures on Microstructures and Mechanical Properties of Sn4.0Ag0.5Cu1.0Ni Solder Alloy - Siti Rabiatull Aisha, Idris; Nadhrah, Murad; M., Ishak (IEEE, 2016)
This research was carried out to investigate the effects of sintering temperature on the properties of Sn-4.0Ag-0.5Cu-1.0Ni solder alloy by varying the temperatures. The Sn-4.0Ag-0.5Cu-1.0Ni solder alloy was prepared by using powder metallurgy method by press and sinter routes. 99.9% of pure Sn, Ag, Cu and Ni powder were used in this research where the pre-mixed powder undergoing milling process for 6 hours using a planetary ball machine. Hydraulic press machine was used to compact the solder powder at identically 5 tons(125 bars) for all samples. Five different temperatures of sintering specifically at 120℃, 150℃, 180℃, 220℃ and 250℃ were used. Characterizations on the microstructures such as grain size, thickness of intermetallic compound and, wettability angle were carried out using Scanning Electron Microscopy. Meanwhile, properties of the solder alloy were also evaluated through hardness and tensile test. It is expected that sintering process could be able to improve the strength of the solder joint by decreasing the intermetallic compound grain size. So far, most papers commonly used 180℃ as their sintering parameter without anyone providing the promising findings and various effects of the temperature onto solder. Therefore, this work is conducted to make a clarification and be the pilot study for the next sintering works for soldering. This paper reports experimental results of properties of Sn-4.0Ag-0.5Cu-1.0Ni solder alloy at different sintering temperatures.